Growth and Nutrition in Cystic Fibrosis - Brownell, Jefferson N.; Bashaw, Hillary; Stallings, Virginia A. (Seminars in Respiratory and Critical Care Medicine, 2019)
Optimal nutrition support has been integral in the management of cystic fibrosis (CF) since the disease was initially described. Nutritional status has a clear relationship with disease outcomes, and malnutrition in CF is typically a result of chronic negative energy balance secondary to malabsorption. As the mechanisms underlying the pathology of CF and its implications on nutrient absorption and energy expenditure have been elucidated, nutrition support has become increasingly sophisticated. Comprehensive nutrition monitoring and treatment guidelines from professional and advocacy organizations have unified the approach to nutrition optimization around the world. Newborn screening allows for early nutrition intervention and improvement in short- and long-term growth and other clinical outcomes. The nutrition support goal in CF care includes achieving optimal nutritional status to support growth and pubertal development in children, maintenance of optimal nutritional status in adult life, and optimizing fat soluble vitamin and essential fatty acid status. The mainstay of this approach is a high calorie, high-fat diet, exceeding age, and sex energy intake recommendations for healthy individuals. For patients with exocrine pancreatic insufficiency, enzyme replacement therapy is required to improve fat and calorie absorption. Enzyme dosing varies by age and dietary fat intake. Multiple potential impediments to absorption, including decreased motility, altered gut luminal bile salt and microbiota composition, and enteric inflammation must be considered. Fat soluble vitamin supplementation is required in patients with pancreatic insufficiency. In this report, nutrition support across the age and disease spectrum is discussed, with a focus on the relationships among nutritional status, growth, and disease outcomes.
Keywords: malnutrition; fat-soluble vitamins; pancreatic insufficiency; energy balance; pancreatic enzyme replacement therapy; cystic fibrosis